FRI0041 ULTRASOUND-DETECTED SYNOVITIS AMONG INDIVIDUALS AT RISK OF RHEUMATOID ARTHRITIS INCREASES THE RISK OF DEVELOPING CLINICAL ARTHRITIS. (2nd June 2020) - Hanova, P.; Prajzlerová, K.; Petrovská, N.; Gregová, M.; Mann, H.; Pavelka, K.; Vencovský, J.; Šenolt, L.; Filková, M.
Abstract : Background: During the transition to rheumatoid arthritis (RA) patients pass through several phases. In the preclinical phase, the presence of anti citrullinated protein antibodies (ACPA) can be detected [1]. A set of clinical characteristics for patients with arthralgia who are at risk of progression to RA was established (clinically suspected arthralgia; CSA) [2]. Ultrasound (US) is more sensitive diagnostic tool in detecting synovitis than clinical assessment and was recommended to use in diagnostics of RA. Objectives: To test if ultrasound-detected synovitis among patients at risk of progression to RA increases the risk of developing clinical arthritis (CA) in the future. Methods: ACPA+ individuals with arthralgia and/or those fulfilling CSA criteria were enrolled into the study and were assessed in 3 months interval (routine clinical investigation with laboratory tests, 68-joint count, US assessment). Tender and swollen joint counts were provided by an independent investigator. Sonographer was blinded to all clinical and laboratory data. CA was defined as clinically swollen and tender joint. All US assessments were provided by a single experienced investigator. Thirty joints US score was assessed bilaterally in wrist, MCP I-V, PIP II-V (dorsal and palmar approach), MTP II-V (dorsal approach), ankle (dorsal, medial and lateral approach). US synovitis was defined according the EULAR-OMERACT and scored separately in gray-scale (GS) 0-3 (zero to severe synovitis) and Power Doppler (PD) 0-3 (zero to high activity). Scores were calculated as sum scores. For the statistical analysis, we used GraphPad Prism 8.0.0 software (Wilcoxon-Mann-Whitney test), and relative risk ratio (RR). Results: 93 patients were enrolled into the study (95% female). 58 patients were ACPA+ (all of them RF+), 35 were ACPA- (10 of them RF+). Of ACPA+ individuals, 100% fulfilled the CSA criteria, all seronegative individuals met the CSA criteria. At baseline, GS≥1 was detected in 69 patients (74%), PD≥1 was in 26 (28 %) patients. Single erosion was found by US in 1 patient (0, 9%) at baseline. 14 patients (15%) developed CA within 30 months, 77% of them till month 10 from the baseline. No statistical difference in US synovitis score was found between ACPA+ vs. ACPA- and CSA+ vs. CSA- groups at baseline. RR to develop CA at the joint level in patients with GS≥1 at baseline was 1.37 (95% CI 0.99-1.89; p<0.05), with PD≥1 the RR was 2.5 (95% CI 1.3-4.8; p<0.05), in GS≥2 RR was 3.8 (95% CI 2.6-5.6; p<0.0001), in PD≥2 RR was 5.3 (95% CI 2.4-11.7; p<0.0001). US-detected synovitis preceded clinical finding of arthritis by 3 months (SD 1.2). Conclusion: US-detected synovitis in patients at risk of RA further increases the risk of developing clinical arthritis in the future. US detected synovitis in joints appear about 3 months prior synovitis detected by routine clinical assessment. References: [1]Bos, W. H., Wolbink, G. J., Boers, et al. Arthritis development in patients with arthralgia is strongly associated with anti- citrullinated protein antibody status: a prospective cohort study. Annals of the Rheumatic Diseases, 2010;69(3):490-4. [2]van Steenbergen HW, Aletaha D, Beaart-van de Voorde LJJ, et al. EULAR definition of arthralgia suspicious for progression to rheumatoid arthritis. Annals of the Rheumatic Diseases 2017;76:491-6. Acknowledgments: Project AZV-17-32612A Disclosure of Interests: Petra Hanova: None declared, Klára Prajzlerová: None declared, Nora Petrovská: None declared, Monika Gregová Consultant of: Novartis, Abbvie, Paid instructor for: Novartis, Speakers bureau: Novartis, Abbvie, MSD, Heřman Mann: None declared, Karel Pavelka Consultant of: Abbvie, MSD, BMS, Egis, Roche, UCB, Medac, Pfizer, Biogen, Speakers bureau: Abbvie, MSD, BMS, Egis, Roche, UCB, Medac, Pfizer, Biogen, Jiří Vencovský: None declared, Ladislav Šenolt: None declared, Mária Filková: None declared